HLA-G Dimers in the Prolongation of Kidney Allograft Survival - Maureen Ezeakile; Vera Portik-Dobos; Juan Wu; Daniel D. Horuzsko; Rajan Kapoor; Muralidharan Jagadeesan; Laura L. Mulloy; Anatolij Horuzsko (Journal of Immunology Research)
Human leukocyte antigen-G (HLA-G) contributes to acceptance of allografts in solid organ/tissue transplantation. Most studies have determined that soluble HLA-G isoforms are systematically detected in serum/plasma of transplanted patients with significantly fewer episodes of acute and/or chronic rejection of allogeneic tissue/organ. Current models of the interactions of HLA-G and its specific receptors explain it as functioning in a monomeric form. However, in recent years, new data has revealed the ability of HLA-G to form disulfide-linked dimeric complexes with high preferential binding and functional activities. Limited data are available on the role of soluble HLA-G dimers in clinical pathological conditions. We describe here the presence of soluble HLA-G dimers in kidney transplant patients. Our study showed that a high level of HLA-G dimers in plasma and increased expression of the membrane-bound form of HLA-G on monocytes are associated with prolongation of kidney allograft survival. We also determined that the presence of soluble HLA-G dimers links to the lower levels of proinflammatory cytokines, suggesting a potential role of HLA-G dimers in controlling the accompanying inflammatory state.